Dervain's Negritude: the writing of the negation of selfand the writing of the other - Bouatenin, Adou (Romanica Olomucensia, 2017)
Émile Eugène André Dervain is little known to the general public. This Ivorian author considers himself a negritudian. Indeed, he reclaims the Negritude of the founding fathers to adapt it to his personal life. In addition, he identifies himself to the world in a movement of sympathy which allows him to die as himself and be reborn as someone else. What does this claim to identity consist of within his poetic texts? In the light of psychocriticism, it is shown that by denying himself, Dervain builds an identity which seems to be his true identity, because the colour of his skin is a colour that has been borrowed Through this metaphor, the personal image of Dervain is that of a poet suffering for being of mixed race. In this paper an attempt is made to give some explanation of the reasons why Dervain denies his first identity in order to adopt a second one, and thus affirms his Ivoirity and the expression of his Negritude.
Keywords: Émile Eugène André Dervain; psychocriticism; negritude; writing of negation of self; writing of the other; personal myth; Ivoirity